Harmonizing Formula Prescription Patterns in Patients With Chronic Kidney Disease: A Population-Based Cross-Sectional Study - Lin, Hung-Lung; Lin, Ming-Yen; Tsai, Cheng-Hsun; Wang, Yi-Hsiu; Chen, Chung-Jen; Hwang, Shang-Jyh; Yen, Ming-Hong; Chiu, Yi-Wen (Frontiers in Pharmacology, 2021)
Objective: Harmonizing formulas are associated with beneficial renal outcomes in chronic kidney disease (CKD), but the therapeutic mechanisms are unclear. The study aims to explore the associations of intentions and independent factors with harmonizing formulas prescriptions for patients with CKD. Methods: We conducted a population-based cross-sectional study to explore factors associated with harmonizing formulas prescription. Patients who had been prescribed harmonizing formulas after CKD diagnosis was defined as the using harmonizing formulas group. Disease diagnoses when having harmonizing formula prescriptions and patient characteristics related to these prescriptions were collected. Results: In total, 24,971 patients were enrolled in this analysis, and 5,237 (21%) patients were prescribed harmonizing formulas after CKD diagnosis. The three most frequent systematic diseases and related health problems for which harmonizing formula prescriptions were issued in CKD were symptoms, signs, and ill-defined conditions (24.5%), diseases of the digestive system (20.67%), and diseases of the musculoskeletal system (12.9%). Higher likelihoods of harmonizing formula prescriptions were associated with young age (adjusted odds ratio: 0.98, 95% confidence interval: 0.97–0.98), female sex (1.79, 1.68–1.91), no diabetes (1.20, 1.06–1.36), no hypertension (1.38, 1.27–1.50), no cerebrovascular disease (1.34, 1.14–1.56), less disease severity (0.85, 0.83–0.88), using nonsteroidal anti-inflammatory drugs (NSAIDs) (1.65, 1.54–1.78), and using analgesic drugs other than NSAIDs (1.47, 1.35–1.59). Conclusion: Harmonizing formulas are commonly used for treating symptoms of the digestive and musculoskeletal systems in CKD cases. Further research on harmonizing formula effectiveness with regard to particular characteristics of CKD patients is warranted.